Using the web for critical learning of al-Qur’an’s ‎language: an ‎‎ exploratory case study - Abdullah, Matin Saad; Pathan, Al-Sakib Khan; Rahman, Muhammad Abdur (2012)
About 80 percent of the world's Muslim populations are non-native speakers of ‎Arabic language. ‎Since ‎it ‎is ‎‎obligatory for all Muslims to recite the Qur'an in ‎Arabic ‎during regular prayers, ‎an ‎‎extraordinary ‎‎social phenomenon has taken ‎place ‎in some parts of the ‎Muslim ‎world: in schools, ‎children are only taught the ‎complex phonetic rules of the ‎Arabic language ‎in ‎the ‎context of the ‎Qur'an. This has ‎given rise to a demographic segment of adult learners who are interested in a ‎‎Language for Specific Purposes (LSP) curriculum that would help them learn ‎a ‎closed set of ‎‎syntactic rules ‎and ‎‎vocabularies in the ‎context ‎of the Qur'an, so that ‎they can recall an idiomatic ‎translation in their native language while they recite or ‎listen to the Qur'an. Little research work ‎exists on the task modeling ‎and user ‎modeling for this purpose. This ‎research work explores the ‎possibilities of ‎using ‎user stereotypes in the creation of ‎task models to be used in development of a ‎‎comprehensive Computer ‎Assisted Language Learning (CALL) module. In this paper, ‎firstly‎, ‎the ‎design and initial ‎‎prototype of a ubiquitous web based ‎‎language learning ‎software is presented and ‎‎some ‎results of the user modeling are ‏shared‎. ‎Secondly‎, ‎changes made to the initial implementation based on the user ‎modeling are presented. And finally, merits and drawbacks of the new implementation ‎are shared.‎‏